2009
DOI: 10.1055/s-0029-1241866
|View full text |Cite
|
Sign up to set email alerts
|

ChronOS Inject in Children with Benign Bone Lesions – Does It Increase the Healing Rate?

Abstract: These preliminary results indicate that chronOS Inject could provide an alternative treatment for benign bone cysts that are unlikely to heal spontaneously due to the patient's age, high risk of instability or pathological fracture due to the lesion's size or location, or lesions that have already been treated several times using other methods without success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…At a higher pH however, apatite precipitation occurs [7]. Both types of CPC have good biocompatibility and are used clinically [8][9][10][11]. Furthermore, promising in vivo results have been shown for monetite based materials [12].…”
Section: Introductionmentioning
confidence: 99%
“…At a higher pH however, apatite precipitation occurs [7]. Both types of CPC have good biocompatibility and are used clinically [8][9][10][11]. Furthermore, promising in vivo results have been shown for monetite based materials [12].…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, our promising results as well as the results of the treatment with Grafton ® [42] and ChronOS ® [43] justify a prospective multicenter study for further evaluation.…”
Section: Discussionmentioning
confidence: 90%
“…During follow-up from one to twenty months ten defects were observed with partial or subtotal absorption of the injected cement. The volume injected ranged from 2-30 ml [43]. …”
Section: Discussionmentioning
confidence: 99%
“…This study showed that 80% of patients had a complete or partial response after treatment. Furthermore Joeris et al used percunateous tricalcium sulphate for bone regeneration and concluded that 96% of patients were with good results [71].…”
Section: Coralsmentioning
confidence: 99%